FAKTOR YANG MEMPENGARUHI KEJADIAN ISPA PADA BALITA DI DESA KEMBANG SARI KEC. JATIBANTENG KAB.SITUBONDO - KARTININGRUM, EKA DIAH (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2016)
ISPA is an acute respiratory illness that is easy to attack the child. Many factors can lead to respiratory infection. The purpose of this study was to determine the factors that influence the incidence of ISPA in Desa Kembang Sari Kecamatan Jatibanteng Kabupaten Situbondo. This study used a case control design with a sample of 38 infants who were selected using purposive sampling. Data collected by interview and observation and then analyzed using chi square test and logistic regression. The results showed that there was no effect of age, gender, nutritional status, and the status of immunization against ARI in infants (p value> 0.05) and found an effects of habit using firewood to ISPA in infants with ? value of 5.030, with OR (153.00) and 95% CI (12.681-1845.919) means that parents who use firewood as the main ingredient of cooking has 153 times greater risk of experiencing ISPA in infants compared with those not using wood as a fuel at a significance level 5%.Keywords : ISPA, firewood, factor, influenced